Care management and mental health. Issue 6880 (20th March 1993) - Thornicroft, G; Ward, P; James, S
Abstract : The community care reforms will produce a new kind of key worker who will organise and budget for packages of care: the care manager. Care management goes live in April 1993 but is still poorly rehearsed and its performance may yet disappoint. This overview sets out the origins of case management, its transformation into care management, and the principles guiding its practice. To spell out how the concept works, plans for care management in Southwark's mental health services are described.